Implementation Of Augmented Reality At State Polytechnic Of Samarinda Building Using Marker Based Tracking Method - Sianipar Yosephine Yulietayanti Natalia; M. F. Andrijasa; Rheo Malani (Journal of Informatics and Computing, 2022)
Augmented Reality (AR) is increasingly used in the industrial revolution 4.0 as it is today, one of which is as a medium for information and learning. Currently, the Samarinda State Polytechnic (POLNES) is one of the universities located in Samarinda and has buildings as a place for lecture activities. The campus introduction media used today is to use miniatures and this is still not effective in providing the right information results. The research with the title "Implementation of Augmented Reality in the Samarinda State Polytechnic building using the Marker Based Tracking Method", aims to help introduce buildings that are used as places for student lecture activities. The benefits of this study can provide convenience to students and the general public who want to know the building plan in the POLNES campus environment. The research method uses the waterfall method with observation and literature data collection techniques. The results of this study are in the form of an android mobile application with Augmented Reality technology that can display the plan of the Samarinda State Polytechnic building along with its information.